Averroè, una traduzione ininterrotta (Doctor Virtualis, 2022)
My collaboration with Massimo Campanini developed around our common interests in the classics of Islamic thought, but with very different approaches, since I am more oriented towards studying the effects and developments they produced on medieval and modern Western thought through a practice of translation that was often creative in terms of inaccuracy – so the opposite of what had been done with respect to Plato and Aristotle.The same Averroes-Ibn Rushd is a fine example of name distortion, and the very formation of his work and the ways in which it was transmitted to the Jewish and Christian world are singular testimonies to the ambiguous outcomes of this translation process. I try to show how the reading of De substantia orbis in the Middle Ages and the Renaissance stimulated not only the rejection of creationism but also pantheistic beliefs, while the famous thesis on the material intellect exposed in the Commentarium Magnum to Aristotle’s De anima stimulated many variants of monopsychism, from Spinoza to Marx and the more recent post-structuralist literature.
Keywords: Ibn Rushd (Averroes); Aristotle; De substantia Orbis; General Intellect